Experimental Validation of a Multidimensional Model for an Indirect Temperature Swing Adsorption Unit. Issue 6 (24th April 2020) - Ried, Thomas; Salazar Duarte, Gabriel; Hinrichsen, Olaf
Abstract: Conventional temperature swing adsorption (TSA) is mainly applied for the removal of trace contaminants. Indirectly heated and cooled adsorbers were developed to make bulk separation economically feasible. A quasi‐continuous TSA process to remove CO2 from an N2 /CO2 mixture with a pilot plant is established. The experimentally determined data are taken to validate and to adjust a 2D simulation model. For the validation, the CO2 desorption, the N2 recovery rate as well as the axial temperature profile are compared. The successful model validation can be seen in the good agreement between simulation and experimental results. Moreover, this process is able to separate high amounts of CO2 and to produce a nearly CO2 ‐free product stream. Abstract : With indirectly heated and cooled adsorbers, bulk separation by temperature swing adsorption becomes economically feasible. A three‐adsorber quasi‐continuous process to remove CO2 from an N2 /CO2 mixture is established. The experimentally determined data are used to validate a 2D simulation model.